The German-Jewish Experience Revisited - Aschheim, Steven E. (Perspectives on Jewish Texts and Contexts, 2015)
This volume includes both historical treatments of differing German-Jewish understandings of their experience - their relations to their Judaism, general culture and to other Jews - and contemporary reflections and competing interpretations as to how to understand the overall experience of German Jewry.